2011
DOI: 10.1289/ehp.1002775
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Biomarkers of Prenatal Atrazine Exposure and Adverse Birth Outcomes in the PELAGIE Birth Cohort

Abstract: Background: Despite evidence of atrazine toxicity in developing organisms from experimental studies, few studies—and fewer epidemiologic investigations—have examined the potential effects of prenatal exposure.Objectives: We assessed the association between adverse birth outcomes and urinary biomarkers of prenatal atrazine exposure, while taking into account exposures to other herbicides used on corn crops (simazine, alachlor, metolachlor, and acetochlor).Methods: This study used a case-cohort design nested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(135 citation statements)
references
References 23 publications
4
121
0
10
Order By: Relevance
“…A study in a French cohort showed the association between the presence of low-dose ATZ metabolites in pregnant mothers and low birth weight in newborns (55). This study raises the possibility that exposure to ATZ can directly alter the fetal developmental program and that ATZ-induced effects can be inherited across generations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in a French cohort showed the association between the presence of low-dose ATZ metabolites in pregnant mothers and low birth weight in newborns (55). This study raises the possibility that exposure to ATZ can directly alter the fetal developmental program and that ATZ-induced effects can be inherited across generations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study showed that ATZ also affects DNA methylation in plants (38). In mammals, ATZ exposure affects many tissues, including testes (3942), ovaries (4347), brain (48,49), liver (5054) and the presence of low dose metabolites of ATZ is associated with low birth weight in human (55). …”
Section: Introductionmentioning
confidence: 99%
“…Atrazine is a herbicide used for the control of broadleaf weeds in the maize, sorghum and sugar cane agricultural industries. Epidemiological studies showed a correspondence between elevated atrazine levels in drinking water and low sperm volume and motility 10 , foetal growth defects, including restriction 11 , small-for-gestational-age 12 and intrauterine growth retardation 13 , foetal gastroschisis 14 and increases in limb reductions (upper and lower), hypospadias and epispadias, cryptorchidism, and spina bifida 15 . Terbuthylazine is a general, broad-spectrum pre-or post-emergence herbicide used in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have linked pesticide exposure to microcephaly and other birth defects [37]. In the case of the insecticide atrazine, one study concluded: "The presence versus absence of quantifiable levels of atrazine or a specific atrazine metabolite was associated with fetal growth restriction… and small head circumference for sex and gestational age…" [38].…”
Section: Mosquito Killing Dilemmamentioning
confidence: 99%